(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This study introduces the notion of the dual BG-algebra. The axioms are presented and are shown to be independent. Fundamental properties of the dual BG-algebra are also provided. The concept of a group-derived dual BG-algebra and its characterization were established. Moreover, a non-group-derived dual BG-algebra can be constructed from a set containing at least 3 elements. Lastly, this paper also presented a Python script used to verify whether a given Cayley table is a dual BG-algebra. This was utilized throughout the process of this study.